Effects of Oil Palm Trunk (OPT), Peat and Coconut Shell Charcoal on the Characteristics of Biomass Pellet - Muftil Badri; Dodi Sofyan Arief; Iwan Kurniawan (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2022)
This paper presents an experimental study of mass percentage and pretreatment effect of oil palm trunk (OPT), and peat charcoal on energy parameters of biomass pellet. The density, calorific value, moisture and ash content of OPT biomass pellet has been developed and the experimental conditions in obtaining the energy parameters of OPT biomass pellet are discussed. The physical pretreatment was carried out by finely chopping OPT, peat charcoal, and adhesive and mixed in a predetermined composition. The manufacturing process of OPT biomass pellet was performed, the mass percentage of OPT and peat charcoal were varied. Type of test was performed on biomass pellet include density, calorific value, moisture and ash content. The influences of various parameters on the characteristics of biomass pellet were considered. The increase of mass percentage and pretreatment of peat charcoal has an effect on increasing the density, decreasing the calorific value of OPT biomass pellet, increasing the moisture content, and increasing the ash content of OPT biomass pellet. The mixture of coconut shell charcoal decreasing the density, increasing the calorific value, decreasing the moisture content, and decreasing the ash content of OPT biomass pellet. Biomass pellets from a mixture of OPT and coconut shell charcoal has a calorific value of 6649 cal/g, where the density was 1.15 g/cm3, the moisture content of 5.6%, and the ash content of 8.9%.